FILTERING AND INGESTION RATES OF THE ANTARCTIC KRILL, Euphausia superba DANA (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - KATO, Mitsuo; SEGAWA, Susumu; TANOUE, Eiichiro; MURANO, Masaaki (1982)
P(論文) departmental bulletin paper